From the land to the Supreme Court, and back again: Defining meaningful consultation with First Nations in northern British Columbia. - Marsden, Tara (Author); Summerville, Tracy (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2006)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1301936